The dynamics of educational transformation: Empirical insights into how innovation, collaboration, and professional development influence digital resource usage across 81 countries - Liu Yuting; Rabiatul-adawiah Binti Ahmad Rashid; Zhu Xiaoying; Chen Cheng (PLoS ONE, 2026)
This study addresses a critical gap in understanding how teacher innovation drives the utilization of digital resources in education, mediated by teachers’ self-efficacy and collaboration, and moderated by professional development. Using data from 68,054 teachers across 81 countries in the PISA 2022 teacher questionnaire, we retained an analytic sample of 64,852 teachers after applying inclusion criteria and listwise deletion of missing values. We employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze these relationships. Results reveal that teacher innovation significantly predicts digital resource usage, with self-efficacy and collaboration serving as key mediators. Professional development amplifies these relationships. This study offers novel insights into the mechanisms linking teacher attributes to digital resource adoption, providing actionable strategies for policymakers to enhance educational digitalization. This study moves beyond the conventional individual-centered perspective of the technology acceptance model, offering a comprehensive and systematic strategy to support the digital transformation of education.